SOURCES OF FINANCING AND THEIR IMPACT ON FINANCIAL SAFETY: AN APPLIED STUDY ON A SAMPLE OF PRIVATE BANKS LISTED IN IRAQ STOCK EXCHANGE - Abdullah Kazem Hassan Al-Saidi; Dergham Sahib Abbas (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The current research seeks to identify the impact of funding sources as a variable on financial safety, and in order to achieve the goal of the research, the Iraqi Stock Exchange was chosen as an applied field represented by private banks, and the research sample included (10) private banks and on the basis of a time series of (10) years. The results were reached using a statistical program such as (SPSS.V.25) to analyze the data to reach conclusions, the most prominent of which was the existence of a correlation and impact relationship between funding sources and financial soundness.